Application and Evaluation of the Framework for Gamification of Educational Systems Using Behavioral Analysis - Gomes, Fernanda Pereira; Brito, Parcilene Fernandes de; Fagundes, Fabiano; Tives, Heloise Acco; Canedo, Edna Dias (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2020)
The development of systems using gamification in the educational context has shown significant improvements in student engagement levels in relation to the content covered during the classes. Therefore, it is important to understand the behavioral variations of users in educational environments, enabling the definition of game elements that stimulate desirable behaviors during the teaching / learning process. This paper presents the proposal of a Framework, entitled Educa3C, developed according to the concepts of Three-Term Contingency of Behavioral Analysis and Gamification. Educa3C has been tested in a module of an educational platform that assists students and teachers in the teaching and learning process of a Propositional Logic discipline. The initial results are satisfactory and the proposed framework can be applied in any educational context or discipline.